2017
DOI: 10.1016/j.cellsig.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular role of DNA damage repair protein APE1 in regulation of IL-6 expression

Abstract: The human apurinic/apyrimidinic endonuclease 1 (APE1) is a pleiotropic nuclear protein with roles in DNA base excision repair pathway as well as in regulation of transcription. Recently, the presence of extracellular plasma APE1 was reported in endotoxemic rats. However, the biological significance and the extracellular function of APE1 remain unclear. In this study, we found that monocytes secrete APE1 upon inflammatory challenges. Challenging the monocytic cells with extracellular APE1 resulted in the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 65 publications
0
47
1
Order By: Relevance
“…In order to evaluate a possible role for secreted APE1 in HCC, we tested whether exogenous addition of recombinant purified APE1 (rAPE1) may trigger a pro-inflammatory status in JHH-6 HCC cell line, as recently demonstrated in human monocytes cell lines [19]. In addition to the wild-type protein (rAPE1 WT ), we used an acetylated-mimicking mutant on residues 27, 31, 32, 35 (rAPE1 K4pleA ), in which Lys residues have been replaced by Ala, as described before [23, 24] and whose relevance in cancer have been recently demonstrated [22] (Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to evaluate a possible role for secreted APE1 in HCC, we tested whether exogenous addition of recombinant purified APE1 (rAPE1) may trigger a pro-inflammatory status in JHH-6 HCC cell line, as recently demonstrated in human monocytes cell lines [19]. In addition to the wild-type protein (rAPE1 WT ), we used an acetylated-mimicking mutant on residues 27, 31, 32, 35 (rAPE1 K4pleA ), in which Lys residues have been replaced by Ala, as described before [23, 24] and whose relevance in cancer have been recently demonstrated [22] (Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Other recent data demonstrated that the redox-function of APE1 may contribute to the control of the inflammatory response by inhibiting the TNF-α-induced endothelial inflammation via thiol-disulfide exchange in TNFR [18]. Moreover, very recently, a role for extracellular APE1 in the control of early stages of inflammation processes has been proposed [19]. Treatment of human THP-1 and RAW264.7 monocytes with rAPE1 increased the expression and secretion of the pro-inflammatory cytokine IL-6, through the involvement of NF-κB transcriptional activation, eliciting an autocrine/paracrine cellular response in a functional feedforward loop between APE1 and IL-6 regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nath and colleagues demonstrated that AP endonuclease is released as extracellular vesicles by monocytes in response to inflammation. Then, APE1 is associated with the cell surface of monocytes, increases the expression and secretion of IL-6, and modulates the inflammatory response [94]. Therefore, it was shown that subsequent production of IL-6 stimulates APE1 translocation from the nucleus to the cytoplasm and additionally increases AP endonuclease secretion [91,94].…”
Section: The Extracellular Role Of Ape1 In Regulating Ros Levels and mentioning
confidence: 99%
“…In hyperacetylation condition, APE1/Ref-1 can be secreted from human embryonic kidney 293 (HEK293) cells [11] and vascular endothelial cells [16]. It also was proposed that APE1/Ref-1 is secreted from monocytes in response to lipopolysaccharide [17]. The ApoE knockout mouse (ApoE −/− ) model is widely used to investigate the pathogenesis of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%